Towers of midnight - Jordan, Robert, 1948-2007; Sanderson, Brandon (Jordan, Robert, 1948-2007. Wheel of time, 2010)
As the seals on the Dark One's prison crumble and the armies of the Shadow boil out of the Blight, Perrin Aybara, hunted by specters from his past, must seek answers in "Tel'aran'rhiod" and find a way to master the wolf within him -- or lose himself to it forever. Meanwhile, Matrim Cauthon prepares for the most difficult challenge of his life ... as The Tower of Ghenjei awaits.